Linking Ross Sea Coastal Benthic Communities to Environmental Conditions: Documenting Baselines in a Spatially Variable and Changing World - Cummings, Vonda J.; Hewitt, Judi E.; Thrush, Simon F.; Marriott, Peter M.; Halliday, N. Jane; Norkko, Alf (Frontiers in Marine Science, 2018)
Understanding the functionality of marine benthic ecosystems, and how they are influenced by their physical environment, is fundamental to realistically predicting effects of future environmental change. The Antarctic faces multiple environmental pressures associated with greenhouse gas emissions, emphasising the need for baseline information on biodiversity and the bio-physical processes that influence biodiversity. We describe a survey of shallow water benthic communities at eight Ross Sea locations with a range of environmental characteristics. Our analyses link coastal benthic community composition to seafloor habitat and sedimentary parameters and broader scale features, at locations encompassing considerable spatial extent and variation in environmental characteristics (e.g. seafloor habitat, sea ice conditions, hydrodynamic regime, light). Our aims were to: (i) document existing benthic communities, habitats and environmental conditions against which to assess future change, (ii) investigate the relationships between environmental and habitat characteristics and benthic community structure and function, and (iii) determine whether these relationships were dependent on spatial extent. A very high percentage (>95%) of the between-location variability in macro- or epifaunal community composition was explainable using multi-scale environmental variables. The explanatory power varied depending on the scale of influence of the environmental variables measured (fine and medium-scale habitat, broad scale), and with community type. However, the inclusion of parameters at all scales produced the most powerful model for both communities. Ice duration, ice thickness and snow cover were important broad scale variables identified that directly relate to climate change. Even when using only habitat-scale variables, extending the spatial scale of the study from three locations covering 32 km to eight locations covering 340 km increased the degree of explanatory power from 18-32% to 64-78%. The increase in explanatory power with spatial extent lends weight to the possibility of using an indirect ‘space for time’ substitution approach for future predictions of the effects of change on these coastal marine ecosystems. Given the multiple and interacting drivers of change in Antarctic coastal ecosystems a multidisciplinary, long term, repeated observation approach will be vital to both improve and test predictions of how coastal communities will respond to environmental change.